Malignant trichilemmal carcinoma misdiagnosed with parotid gland malignant tumor. (February 2023) - Terenzi, Valentina; Martellucci, Salvatore; Dal Cortivo, Fiorenza; Stolfa, Andrea; Fiorentino, Francesco; Clemenzi, Veronica; Gallo, Andrea; Valentini, Valentino; Pagliuca, Giulio
Highlights: Malignat proliferating trichilemmal tumor (MPTT) are rare tumors usually presenting in photo-exposed areas, especially on the face, scalp, neck, and dorsal part of the hand; Differential diagnosis include squamous cell carcinoma, basal-cell carcinoma, keratoacanthoma and malignant nodular melanoma; Resection in free margins is the treatment of choice; Adijuvant radiotherapy is indicate in case of high-risk tumors. Abstract: Malignat proliferating trichilemmal tumor (MPTT) are rare tumors usually presenting in photo-exposed areas, especially on the face, scalp, neck, and dorsal part of the hand. Differential diagnosis include squamous cell carcinoma, basal-cell carcinoma, keratoacanthoma and malignant nodular melanoma, so that only incisional biopsy can lead to pre-operative diagnosis. We present case MPTT misdiagnosed with parotid gland malignant tumor that underwent radical surgical excision and adijuvant radiotherapy.